Legacy of summer drought on autumnal leaf litter processing in a temporary mediterranean stream - Mora-Gómez, Juanita (2020)
Electronic supplementary material: The online version of this article (https://doi.org/10.1007/s10021-019-00451-0) contains supplementary material, which is available to authorized users